Critical Evaluation of the Current Bonus and Merits Policy and Its Impacts on Employees’ Pay Satisfaction: Reference to Two Oil and Gas Service Companies - Othman Alyafei (Current Aspects in Business, Economics and Finance Vol. 8, 2023)
This research explores the relationship between the current Bonus & Merit (B&M) policy along with its effects, if any, and pay satisfaction (PS) of the employees working in two oil and gas service companies. It should be noted that once satisfied in terms of pay, working staff are expected to deliver much more intensely at all levels so that the company realizes its objectives. With this notion in mind, the study aims to explore in-depth ways and means to get to the desired level of pay satisfaction that suits the working staff. The research seeks to conceptualize various associated dimensions generated from an extensive literature review aiming to prove or otherwise the sets of hypotheses and research questions. A sequential explanatory mixed methods research pattern is employed. The study findings indicate the importance of analysing all associated dimensions that are generated from and within the content of the B&M policy. This impacts the employees’ level of PS, and accordingly their expected productivity. In other words, the terms and contents of the B&M policy need to be viewed differently, in accordance with the study findings so that the objectives are realized.